La festividad religiosa del señor del auxilio y su contribución a la identidad cultural en el distrito de Chocope, provincia de Ascope: 2018. - Acevedo Arana, Rosa María (2018)
This thesis was carried out with the purpose of explaining how the religious festival of the Lord of Help contributes towards the cultural identity of the inhabitants of the District of Chocope, Province of Ascope: 2018. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 64 inhabitants; with which we worked applying the inductive-deductive and analytic-synthetic methods, techniques of direct observation, participant observation and interview and instruments such as the questionnaire and field notebook. The results obtained from this research around the religious festival of the "Lord of Help", show that the villagers identify with a great devotion to their patron saint, participating in activities organized by the Brotherhood; like the masses, novenarios, processions, gastronomy, dances, contest of dances, etc .; in which I participated, in this way I was able to analyze the influence of religious festive rituals and describe the religious, social and cultural activities in honor of the "Lord of Help"; Thanks to the technique of participant observation is known objectively that reality is based on faith and belief, demonstrating the brotherhood that exists among the Chocopanos.